PENGARUH PEMBELAJARAN DARING DAN LURING TERHADAP MOTIVASI BELAJAR PESERTA DIDIK - Harun; Burhanuddin; Hardianto Rahman (Universitas Islam Ahmad Dahlan, 2022)
This study aims to knowing effect of online learning on students' learning motivation, knowing effect of online learning on students' learning motivation, knowing effect of simultaneous online and offline learning on students' learning motivation in Islamic religious education subjects at SMK Negeri 1 Sinjai. This research is included in the type of ex post facto research using a quantitative research approach. The population in this study were all students of class X SMKN 1 Sinjai, while the sample consisted of 80 students. The data collection techniques used in this study were questionnaires and documentation, while the data analysis used multiple regression analysis techniques.The results of this study indicate that the effect of online learning on learning motivation is 0.029. The significance value of obtained is smaller than (0.029 > 0.05), there is an effect of offline learning on learning motivation of 0.010. The significance value of obtained is smaller than (0.010 > 0.05), there is an effect of simultaneous online learning and offline learning on learning motivation. Based on the value of Fhit = 23,095> Ttable = 2,720. The effect of the independent variable Online Learning and Offline Learning on the independent variable Learning Motivation of Learners is 35.9%. While the remainder (100%-35.9% = 64.1%) is influenced by other variables.